Simulated STAT Laboratory in a University Based Program...American Society for Clinical Laboratory Science (ASCLS) Clinical Laboratory Educators’ Conference February 19-21, 2015 in Cincinnati, Ohio - Nicholaou, Matthew; Thomas, Janice; Oja, Janet (Clinical Laboratory Science)
The ability for students to rotate in clinical laboratories can be limited in some university based Medical Laboratory Sciences (MLS) programs. These shorter rotations can be supplemented with extensive simulated laboratory work that often is discipline specific. A course was developed to replicate the environment of a clinical STAT laboratory and enhance students' exposure to this type of multi-discipline work setting. The simulated STAT laboratory consists of five areas: receiving and specimen processing, chemistry, hematology, urinalysis, and microbiology. Students are given scenarios related to customer service, workflow, instrument maintenance and troubleshooting, time management, data entry, and result reporting; thus addressing the specific training needs expressed by an advisory board represented by local clinical affiliates. In the summer of 2014 this laboratory was renovated and equipped with new instrumentation, including a Laboratory Information System (LIS). Students rotate each week between the five areas of the lab and two students are selected to act as laboratory managers. Specimens are dropped off at the beginning of each laboratory section and students are required to accession, process, analyze, and report the results of these samples. Students are graded on the timely and accurate reporting of results, as well as compliance with a number of laboratory tasks such as quality control. A pre and post survey consisting of 12 questions addressing the main educational outcomes of this course was given and showed that students felt more confident in performing a variety of laboratory testing under real-world conditions after taking the course.